Synthesis and Crystal Structure of Bis-(μ2-(4-Carboxybenzyl)-methylene-4-pyridine-O,O’)-dibromo-cadmium Complex - You, Xiuli; Hu, Tao (Asian Journal of Chemistry, 2012)
Reaction of one equivalence of CdBr2 and two equivalence of zwitter ionic carboxylate (4-carboxybenzyl)-methylene-4-pyridine ligand in water give rise to the complex [C26H22N2O4CdBr2] (I), in which the central Cd atom adopts a distorted octahedral coordination geometry that is formed from four O atoms of two bidentate (4-carboxybenzyl)-methylene-4-pyridine ligands and two Br atoms.